Ranger's Apprentice Book One The Ruins of Gorlan - F Flanagan, John (New York Puffin Books, 2006)
When fifteen-year-old Will is rejected by battleschool, he becomes the reluctant apprentice to the mysterious Ranger Halt, and winds up protecting the kingdom from danger
1
Keywords: Fantasy; Heroes